0564 Effect Of Oral Appliance Therapy In Moderate And Severe Obstructive Sleep Apnea: Prospective Multi-center Observational Study. (12th April 2019) - Kim, Jeong-Su; Kim, Dong-Ha; Byun, Jung-Ick; Yang, Kwang-Ik; Cho, Yong Won; Shin, Won Chul
Abstract: Introduction: Oral appliance (OA) is an effective treatment option for mild to moderate obstructive sleep apnea (OSA) patients. It is also recommended for severe OSA patient when they fail continuous positive airway pressure (CPAP) treatment. However, the effect of OA as a first-line treatment for severe OSA patients has not been properly evaluated. This study aimed to evaluate the effect of OA in newly diagnosed moderate to severe OSA patients. Methods: This was a prospective study performed at three sleep centers in Korea (Keimyung University Dongsan Medical center, Soon Chun Hyang University hospital Cheonan, and KyungHee University Hospital at Gangdong). Adult OSA patients with moderate to severe severity (AHI≥15) were recruited. They were treated with customized two-piece dental device. Sleep questionnaire and video-polysomnography were performed before and 1 month after the treatment. The primary outcome measure was improvement in apnea-hypopnea index (AHI) at 1 month after the dental device. Secondary end-points were improvement of sleep questionnaire and sleep structure. Results: Total 50 patients were enrolled between Mar 2017 and Aug 2018. Two were excluded for having dental problems, 1 withdrew to participate, and 2 patients dropped out, and remaining 45 patients were analyzed. Mean age was 47.4±12 years old, and 43 (95.6%) were male with mean BMI of 26.8±3.3, and AHI of 29.8±11.0/hr. Twenty-two of the patients had moderate OSA and the rest had severe OSA (AHI≥30). At 1 month follow-up, mean AHI decreased significantly (pre: 29.8±11.0, post 11.6±10.7, p<0.001) with the OA. The improvement was similar between the moderate and severe OSA, and 70.8% of the severe OSA patients had more than 50% improvement in AHI. The proportion of deep sleep increased (pre: 14.5±13.4%, post 19.1±15.7%, p=0.004), and wake after sleep onset decreased (pre: 59.9±52.3min, post 38.8±31.8min, p=0.011). BMI was independent factor associated with percent improvement in AHI. Conclusion: The result of this study shows that OA is as effective in severe OSA as in moderate OSA patients. Support (If Any): None